Susceptibility to peer pressure and attachment to friends - Lotar Rihtarić, Martina (Array, 2013)
The role of attachment to friends in the explanation of adolescents’ susceptibility to peer pressure was explored, regarding the way these two constructs are measured. In Study 1, 475 high school students (194 boys and 281 girls) were given Susceptibility to Peer Pressure Questionnaire, and their attachment to friends was measured with Modified Experiences in Close Relationships Inventory and Relationship Scales Questionnaire. One month later, 80 boys and 80 girls participated in Study 2, where they completed the same Susceptibility to Peer Pressure Questionnaire in a chat-room simulation, convinced that they can see other students’ answers and that their own answers could be seen by others. When susceptibility to peer pressure was measured by self-report questionnaire, the level of avoidance proved to be a significant predictor for boys, while the level of anxiety and the model of others were significant predictors for girls. When susceptibility to peer pressure was measured experimentally, the results showed that attachment dimensions predict only girls’ susceptibility and that the only significant predictor is their model of others.